1998
DOI: 10.1084/jem.187.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis in Chlamydia-infected Cells: Blockade of Mitochondrial Cytochrome c Release and Caspase Activation

Abstract: We report that chlamydiae, which are obligate intracellular bacterial pathogens, possess a novel antiapoptotic mechanism. Chlamydia-infected host cells are profoundly resistant to apoptosis induced by a wide spectrum of proapoptotic stimuli including the kinase inhibitor staurosporine, the DNA-damaging agent etoposide, and several immunological apoptosis-inducing molecules such as tumor necrosis factor-α, Fas antibody, and granzyme B/perforin. The antiapoptotic activity was dependent on chlamydial but not host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
508
4
10

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(550 citation statements)
references
References 68 publications
28
508
4
10
Order By: Relevance
“…On the other hand, a recent study 73 has shown that chlamydial infection inhibits apoptosis in the host cell. Therefore, the presence of infection with chlamydia and mycoplasma may explain the proliferation of smooth muscle cells and the fact of their monoclonality 74,75 in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a recent study 73 has shown that chlamydial infection inhibits apoptosis in the host cell. Therefore, the presence of infection with chlamydia and mycoplasma may explain the proliferation of smooth muscle cells and the fact of their monoclonality 74,75 in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 98%
“…21 Although the mechanism by which infection with C. pneumoniae may increase the risk of lung cancer is not known, one possible explanation is that it may induce irregular apoptosis in tissues. 22 The human SRSF6 protein has also been linked to infection with HIV-1, reportedly regulating HIV-1 mRNA processing and possibly being involved in nuclear export of spliced mRNAs. 23,24 L3MBTL1, on the other hand, is a tumor suppressor gene that appears to suppress genes and microRNAs that re-activate during tumor growth and whose expression is associated with decreased risk of death due to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the cell must remain viable during infection. C. trachomatis has been shown to promote host cell survival by actively inhibiting the mitochondrial pathway of apoptosis, in part by triggering proteasomal degradation of proapoptotic factors within the cell (8,(10)(11)(12)41). Even host cell division may pose challenges to C. trachomatis replication, since important nutrients may be consumed as the cell divides.…”
mentioning
confidence: 99%